El síndrome de Asperger y su incidencia en la inclusión educativa de los niños de 8 años en la escuela particular adventista Gabriela Mistral de la ciudad de Guayaquil durante el periodo lectivo 2015 – 2016 - Medina Vivas, Dévora (2015)
The purpose of this research is to determine the incidence of the syndrome of Asperger educational inclusion of children 8 years of Gabriela Mistral Adventist Private School in the city of Guayaquil, as well as providing g a guide for teachers to stimulate areas affective and social activities through artistic and recreational character, having as a result the development of those skills allowing suit your school group. Methodologically, this study is an inductive research, analytical and synthetic character that by design is a field and allowed to investigate the theoretical foundations of educational inclusion, determine a percentage of teachers who are unaware of techniques and methods on handling Children with Asperger syndrome in the classroom….